2011
DOI: 10.1158/1541-7786.mcr-10-0227
|View full text |Cite
|
Sign up to set email alerts
|

MYCN Sensitizes Human Neuroblastoma to Apoptosis by HIPK2 Activation through a DNA Damage Response

Abstract: MYCN amplification occurs in approximately 20% of human neuroblastomas and is associated with early tumor progression and poor outcome, despite intensive multimodal treatment. However, MYCN overexpression also sensitizes neuroblastoma cells to apoptosis. Thus, uncovering the molecular mechanisms linking MYCN to apoptosis might contribute to designing more efficient therapies for MYCN-amplified tumors. Here we show that MYCN-dependent sensitization to apoptosis requires activation of p53 and its phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 51 publications
6
42
0
Order By: Relevance
“…1h). Further, analysis of the p53 phosphorylation status revealed a lower phosphorylation level of the serine 46 residue in MycN(-) cells, which is in agreement with recently published data on the significance of p53 phosphorylation for apoptosis in MycN overexpressing cells [14]; the extent of phosphorylation was correlated with the level of total p53 (Fig. 1h).…”
Section: Downregulation Ofsupporting
confidence: 92%
“…1h). Further, analysis of the p53 phosphorylation status revealed a lower phosphorylation level of the serine 46 residue in MycN(-) cells, which is in agreement with recently published data on the significance of p53 phosphorylation for apoptosis in MycN overexpressing cells [14]; the extent of phosphorylation was correlated with the level of total p53 (Fig. 1h).…”
Section: Downregulation Ofsupporting
confidence: 92%
“…p53 is actively involved in the apoptosis-sensitive phenotype induced by MYCN. Indeed, MYCN increases p53 transcription [20] and it also induces stabilization of the p53 protein and its proapoptotic kinase HIPK2 via an oncogene-dependent DNA damage response (DDR) [13]. The high levels of mitosis/karyorrhexis and the initial responses to the induction chemotherapy shown by the majority of newly diagnosed MNA NBs are consistent with the integrity of the HIPK2-p53 axis observed in primary NBs [13].…”
Section: Introductionmentioning
confidence: 66%
“…Studying this paradox is likely to uncover molecular mechanisms potentially relevant for the therapy of MNA NBs. Indeed, by these means several groups, including ours, highlighted the p53 pathway as a potential target for MNA NB therapy [13], [14], [15].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…We speculate that this might be due to the presence of the wild-type TP53 in RH18 cells. It was reported that MYCN can regulate TP53 transcription, expression, and activation in human neuroblastoma cells (40,44). For example, high TP53 expression was positively correlated with MYCN expression and amplification in immunohistochemical analysis of neuroblastoma tumors (45).…”
Section: (T) (T) 10 (N) and 1μm (N) For 1 3 And Days B: Sub-conmentioning
confidence: 96%